Mapping municipal food supply: A longitudinal‐spatial case study in Southern Germany - Elena Mager; Martin Ritter; David Sipple; Heiner Schanz (Urban Agriculture & Regional Food Systems)
Abstract German food supply structures show heavy market concentration, which is often framed as a result of economies of scale and scope, individual purchasing behavior, and restrictive EU regulations. However, it remains open how these general developments influenced local food economies and their supply structures of end consumers in small–medium sized municipalities. This paper explores the evolution of local food supply structures on the spatial and temporal scale by mapping food‐supplying businesses in two typical cases, Leutkirch im Allgäu and Waldkirch im Breisgau. The comparative study shows how business‐to‐consumer structures such as food service, retail, and artisanal food processing have developed in terms of numbers of businesses, composition, and spatial distribution. Results show a sharp decline in the diversity and number of enterprises in small and medium‐sized towns. There has also been a shift of enterprises from the city center to the outskirts, for example, in the food service sector. The analysis reveals dynamics that result from a complex interplay of socioeconomic, technological, and local factors. The findings could prove particularly useful for the development of local food policies, strategies, and/or governance aiming at sustainable local food systems and could therefore have implications for their focus.